Bulky monodentate biphenylarsine ligands: Synthesis and evaluation of their structure effects in the palladium-catalyzed Heck reaction - Quinteros, Gisela Julieta (2015)
Biphenyl-based arsine ligands were prepared in two-step fashion by Pd-catalyzed arsination and microwave-assisted Suzuki-Miyaura coupling, providing sterically demanding arsine ligands in overall isolated yields up to 82 % as air-stable solids. Short reaction times were achieved with the assistance of microwave irradiation in the direct and simple described protocol for the synthesis of biarylarsine ligands. The activities of the biphenyl arsine ligands were explored in Pd-catalyzed Heck coupling. As a general trend, the ligands with "blocked" ortho-positions on the non-arsine-containing ring of the biphenyl backbone performed more efficiently in the coupling reaction. This catalytic system allowed several interesting stilbenes to be obtained in very good yields. Sterically demanding biphenyl-based arsine ligands were prepared in high overall yields by microwave-assisted Suzuki-Miyaura coupling. The ligands were evaluated in the Pd-catalyzed Heck coupling reaction; the most active were those with "blocked" ortho-positions on the non-arsine-containing ring of the biphenyl backbone.